Konstruksi Metode Tafsir Ijmali: Kajian Terhadap Kitab At-Tafsir Al-Muyassar Karya ‘Aidh Al-Qarni - Sufian Suri; Andri Nirwana AN (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Construction of The Ijmali Interpretation Method: A Study of The At-Tafsir Al-Muyassar Book of 'Aidh Al-QarniThis study attempts to explain the construct of ijmali interpretation in the book of commentary Al-Muyassar by 'Aidh Al Qarni. Using qualitative research methods with literature studies, this study found that the construct of ijmali interpretation in the book of Al-Muyassar commentary by 'Aidh Al Qarni tends to highlight the style of Sufi interpretation, the mention of the verse in its entirety; namely by first mentioning the verse in full and then interpreting it in its entirety, direct interpretation without using a language approach; such as language style, ta'bir, lafadh forms, dhamir, fi'il and so on. The technique and systematics of the Ijmali method used in the interpretation of Muyassar by 'Aidh Al Qarni is to explain the verses and letters according to the order of the mushḫaf. 'Aidh al-Qarni also interprets verses that are interpreted globally in the form of an interpretation using several series, namely by mentioning the name of the letter in each explanation of the interpretation. The advantages of Muyassar's interpretation in his interpretation use straightforward, clear and easy-to-understand language. While the weakness is not mentioning the sanad when quoting the hadith as a reference